Innovation of Environmentally Friendly Solid Electrolyte Biobattery Based on Carrageenan and Rotten Tomatoes - Widyaningsih, Mia; Abidin, Muhamad; Hafidh, Ashary Fathul; Murniati, Anceu; Ragadhita, Risti; Rizky, Karina Mulya; Mudzakir, Ahmad (Universitas Pendidikan Indonesia (UPI), 2024)
This research aims to create and evaluate the performance of environmentally friendly biobattery based on carrageenan and rotten tomatoes to reduce B3 waste. To make a biobattery based on carrageenan and rotten tomatoes, five ratios of carrageenan and rotten tomatoes mixtures were used with the composition of carrageenan values of 1, 2, 3, 4, and 5% for each type of battery. The parameters observed in this study were the potential difference, current strength, and stability of the biobattery. Carrageenan was added to prevent battery leakage and maintain battery stability. As a result, the biobattery has a potential difference value equivalent to a commercial battery, namely 1.5 V, but the current generated is still low. On the other hand, biobatteries can be applied to alarm clocks. The difference in carrageenan concentration has no significant effect on the value of potential difference, current strength, power, recharging ability, and application on wall clocks, as well as the stability of the biobattery. The experiment was carried out with the hypothesis that husk ash can absorb rotten tomatoes, preventing electrolyte leakage. However, the resulting biobattery is still leaking. After that, we modified it again by using electrolytes made from rotten tomatoes and coconut dregs, but the leakage was still the same. Therefore, the biobattery made from a combination of carrageenan and rotten tomatoes was assumed to keep the battery more stable and prevent leakage. This research was expected to contribute to the development of environmentally friendly batteries to reduce B3 waste, along with the increasing need for batteries in the era of industrial revolution 4.0.